PARTICIPATORY SOFT SKILLS INTERVENTION FOR YOUTH EMPOWERMENT IN MULTICULTURAL RURAL COMMUNITIES: ADVANCING A PANCASILA VILLAGE MODEL IN INDONESIA - Agung Stiawan; Aditya Chandra Setiawan; Raden Roro Maha Kalyana Mitta Anggoro; Hasna Nur Lina (SUBSERVE: Community Service and Empowerment Journal, 2026)
This study examines the effectiveness of a participatory soft skills intervention in strengthening youth capacity within a multicultural rural community to support the development of a Pancasila Village in Indonesia. The program was conducted in Sugihwaras Village, Lamongan Regency, over an eight-month period using a Participatory Action Research (PAR) framework. A total of 30 youth participants, along with village stakeholders, were actively involved in the intervention. The program integrated experiential learning strategies, including leadership training, communication skill development, multicultural dialogue, and conflict resolution simulations. Data were collected through a mixed-method approach, combining pre-test and post-test assessments, observations, and participant feedback. The findings indicate significant improvements across four key competencies: understanding of Pancasila values (from 58% to 85%), communication skills (60% to 88%), multicultural awareness (55% to 84%), and collaborative leadership (50% to 82%). These results demonstrate that experiential and participatory approaches effectively facilitate both cognitive and behavioral transformations among youth. Furthermore, the establishment of the “Pancasila Youth Community” reflects a transition from structured intervention to sustainable, community-driven social action. The study contributes to the literature by proposing an integrative model that combines soft skills development, civic value internalization, and participatory engagement as a unified framework for youth empowerment. This model offers both theoretical and practical implications, particularly for community-based education and social cohesion in diverse societies. Future research is recommended to explore the long-term sustainability and adaptability of this model across different socio-cultural contexts.